The marketing strategies of making Kinabalu Park as a tourism heritage / Doris Day Stephen Nyamok - Stephen Nyamok, Doris Day (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2000)
Established 36 years ago, Kinabalu Park has made a name for itself in the eyes of nature tourism and outdoor adventures. This is especially true for Kinabalu Park as it is expected to entertain the expanding tourism industry and the changing World of International Tourism. Kinabalu Park is funded by the Government and is entrenched within the bureaucratic system. Tourism is one the facets of a Park's development and this should not be allowed to take precedence over other more important values. This includes flora and fauna preservation, watershed and landscape protection, the role of Parks in science and education, and the conservation of endangered species and others. The obvious solution is to strike a balance between conservation and precautionary measures must be adopted so that tourist coming to a park may be satisfied. These factors determines the marketing strategies of making Kinabalu Park as a tourism heritage with areas on marketing opportunities, developing marketing policies, strategies and programs. This study provides comprehensive guidelines for Kinabalu Park. It is the niche of the world market in nature and outdoor recreations that will provide Kinabalu Park with a huge marketing opportunity apart from achieving its objectives and goal for the future generation to see. For the change to occur, politicians and decision makers must be sympathetic and understanding towards this natural 'heritage and needs.